Decision making about esophageal cancer treatment: variation in clinicians' communication behavior: Presenter(s): Loïs van de Water, Amsterdam UMC, Netherlands. (April 2023) - Scholten, Gillian; Henselmans, Inge; van Laarhoven, Hanneke; Smets, Ellen
Abstract : Background: Due to the availability of more than one curative treatment option for esophageal cancer and lack of consensus among clinicians on whether and how to present these treatment options, decision making in this setting can be complex. Moreover, as treatment options often involve multiple treatment modalities, i.e., different combinations of radiation, chemotherapy and/or surgery, treatment decision making also involves multiple clinicians (e.g., radiation oncologists, medical oncologists, surgeons and physician assistants). The aim of this study was to describe how clinicians communicate about treatment decisions with patients with localized esophageal cancer. More specifically, we investigate the variation in whether and how clinicians present a choice, how they communicate pros and cons, if and how they communicate recommendations and how they involve patients in decision making. Methods: For the current analysis, we used audio-recordings of 20 scripted simulated patient assessments from the SOURCE trial [NCT04232735]. Using two highly similar cases, acted by a simulated patient, eliminated variation at patient level. This enabled us to focus on the variation in decision making behavior between clinicians. Audio-recordings were content-coded using open coding, and rated on the degree of shared decision making using the OPTION-12. Findings: Preliminary Findings: show some clinicians leaving the patient no room for choice, some only suggesting the choice not to commit to the advice, and others presenting the patient with a full choice between options. We distinguished 5 different treatment options, ranging from 1 up to 4 options discussed per consultation. Clinicians' expressions regarding choice, patients' role in decision making or an advice were generally implicit. Findings: show OPTION-scores to range from 18.2 to 54.5 (scale 0-100). Discussion: We cautiously conclude that the presented treatment options and the patients' role in the decision making depend on the clinician involved. Final results will be presented in September 2022.